Новые виды пухоедов рода брюэлиа — Brёlia (Mallophaga, Ischnocera) воробьиных птиц Украины - Федоренко, И.А. (Вестник зоологии, 1975)
Three new species of biting lice are described: Brüelia calandrellae sp. n. from Calandrella cinerea Gm., B. kistiakowskyi sp. n. from Anthus campestris L. and B. locustellae sp. n. from Locustella luscinioides Savi. New species are distinguished on the basis of a complex of distinctive morphological characters and parasitism of each species on a specific host.